Measurement of chronic pain in companion animals: Priorities for future research and development based on discussions from the Pain in Animals Workshop (PAW) 2017. (October 2019) - Lascelles, B.D.X.; Brown, D.C.; Conzemius, M.; Gill, M.; Oshinsky, M.L.; Sharkey, M.
Highlights: The estimation of chronic pain in companion animals is a fundamental requirement to advance therapeutic development. To date, most work has centered on owner-completed questionnaires and limb use measures in osteoarthritis. Recent areas of research have extended to developing measures of quality of life (QOL), activity and sensory function. Across all these areas, more data on validity are needed, and studies should be extended to other painful disease states. To facilitate future advances, a collaborative (industry, academia and private practice) approach is proposed. Abstract: The estimation of long-standing pain in companion animals through the measurement of different dimensions impacted by pain is a fundamental requirement if pain management, and pain therapeutic development, are to advance. Although pain management in veterinary medicine has advanced considerably in the last 20 years, there is much critical work to do in the area of measurement of chronic pain. To date, most work has centered on musculoskeletal pain, and has been focused around the measurement of limb use and the development of owner-completed questionnaires, or clinical metrology instruments (CMI). Recent areas of research have extended to developing measures of activity, sensory function (quantitative sensory testing; nociceptive withdrawal reflexes), and quality of life (QoL). Across all these areas, more data on validity are needed, and studies should be extended to other painful disease states. By necessity, assessing measurement tools requires testing in field studies, which incur considerable time and expense. Facilitating these studies could be optimized with a collaborative (industry, academia and private practice) approach, and the utility of the information produced from all field studies would be enhanced by full and transparent reporting and data sharing, including data already generated by industry in the form of studies submitted to the regulatory authorities.